(untitled) (Research, Society and Development, 2022)
Objective: To know the advances described in the literature regarding advances in the field of Brazilian mental health. Materials and Methods: The theme was addressed through an integrative literature review. A survey was carried out in the BDENF, LILACS and SciELO databases. The following descriptors were used combined from two to two: mental health, nursing and disinstitutionization. Scientific articles in the study were Portuguese that made the abstract available in the respective databases and with temporal cut in the last 21 years. Results and Discussion: After data analysis, four categories were identified: Historically constructed mental health, Advances in Brazilian mental health, mental health and primary health care. Final Considerations: The search for support in primary care, as well as psychosocial care centers, the Community Centers, production group, housing, rear (night/holidays/weekends) jointly represent advances in the field of Brazilian mental health, directly reflecting on the care of health professionals.